Small Towns as Beneficiaries of EU Funds (the Example of Warmińsko-Mazurskie Voivodship) - Magdalena Wojarska; Roman Kisiel; Emil Walendzik (Barometr Regionalny)
The objective of this study was to achieve a multidimensional description of the consumption of EU funds by small towns in Warmińsko-Mazurskie voivodship, and to identify the role of this source of funding in the development policy of these localities. The aim was pursued based on secondary data originating from the Local Data Bank of the Central Statistical Office and from the database of the Ministry of Investment and Economic Development (the EU Grants Map), as well as primary data collected during a survey study conducted among representatives of small towns and urban-rural municipalities which contain a small town in their limits (in total 38 units). The percentage of returned and correctly completed questionnaires was 44,74%. The empirical material gathered during the study proves that the budgets of municipalities in Warmińsko-Mazurskie Voivodship in 2006–2016 received PLN 3 244,24 million in the form of grants from the EU and other foreign support programmes, and the share of this sum absorbed by small towns and urban-rural municipalities was 25,91% (PLN 840,44 million), most of which was allocated to urban-rural municipalities (86,61%). Results of the U Mann-Whitney test showed that the distribution of the funds acquired by small towns and urban-rural municipalities with small towns in their limits, calculated per capita, in Warmińsko-Mazurskie Voivodship differed significantly from the sums of money invested by other administrative units of this type in Poland. The research also indicates that the EU funds played an important role in the development policy of small towns, and an opportunity to apply for EU grants had a strong influence on their investment plans.